2017
DOI: 10.1177/0734282917736392
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Disagreement on Emotional and Behavioral Problems in a Sample of Preschool-Age Children

Abstract: The present study aimed to identify predictors of agreement and disagreement concerning emotional and behavioral problems reported by the mothers and teachers of preschool-aged children. Participants included 172 (89 boys) children, their mothers, and their preschool teachers. Mothers were asked to complete the Child Behavior Checklist for Ages 1½-5 (CBCL 1½-5), the Brief Symptom Inventory (BSI), and a sociodemographic questionnaire, and were observed engaging in an interactive task with their child. Preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Even though the cross-informant agreement was modest, there was better agreement on EP than on IP, which is consistent with previous literature [3,17,18,21,22,25,[35][36][37][38][39][40]. The higher level of cross-informant agreement for EP than for IP may be because EP are directly observable and consequently more obvious to report [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Even though the cross-informant agreement was modest, there was better agreement on EP than on IP, which is consistent with previous literature [3,17,18,21,22,25,[35][36][37][38][39][40]. The higher level of cross-informant agreement for EP than for IP may be because EP are directly observable and consequently more obvious to report [17].…”
Section: Discussionsupporting
confidence: 88%
“…Differences in the reports of emotional and behavioural problems, here considered synonyms of Internalizing problems (IP) and Externalizing problems (EP), obtained from different informants are very common. These differences tend to be low to moderate, indicating a modest agreement, which is well established in the literature [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 55%
“…Carneiro et al (6) also found that problem scores on the CBCL were positively associated with maternal psychopathology. Moreover, disagreement between symptoms reported by mothers via the CBCL and symptoms reported by teachers via the CTRF was positively associated with maternal psychopathology (6). Buchmüller et al (2) found mental health status on the scales of anxious/depressed, withdrawal, and attention problems to be in the clinical range on the CBCL as reported by parents.…”
Section: Maternal Psychopathologymentioning
confidence: 94%
“…Given that respondents in part one of Buchmüller et al’s (2) study were refugees, it is plausible that there was an increased prevalence of psychopathology in this sample. Mothers with psychopathology often focus on negative events, recalling them more easily than positive ones, possibly distorting the results of the CBCL (6). Carneiro et al (6) also found that problem scores on the CBCL were positively associated with maternal psychopathology.…”
Section: Maternal Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation